Reduction of hydrogen embrittlement of API 5l X65 steel pipe using a green inhibitor. (14th June 2018) - Soudani, M.; Hadj Meliani, M.; El-Miloudi, K.; Azari, Z.; Sorour, A.A.; Merah, N.; Pluvinage, G.
Abstract: Several inhibitors are used in industry to reduce the corrosive effects of harsh environments on the mechanical properties of steel structures. More recently, eco-friendly (green) inhibitors are being developed to replace the synthetic ones which are known to possess toxic organic molecules. In the present study, Ruta Chalepensis (Fijil) green corrosion inhibitors are utilized with API 5L X65 pipe steel to study their effectiveness in reducing the corrosive effects of HCl acid. Notched specimens are immersed in HCl and HCl with different concentrations of Fijil (3, 5, 10 and 30 vol%), at room temperature and at 80 °C, for periods of 3, 7 and 10 days. Charpy tests are carried out, after each period, on treated (maked in the HCl media with green inhibitor for different concentration) and untreated standard specimens to evaluate the response of the material under dynamic loading. The load-displacement curves are found to consist of four zones corresponding to different crack advance events. The optimum concentration of green inhibitor is found to be 5 vol%. Immersion of API 5L X65 in HCl with 5% green inhibitor is seen to reduce the acid's effect. The improvement of the material's fracture toughness due to the inhibitor was more than 40%. Highlights: Ruta Chalepensi green corrosion inhibitor is use to protect API 5L X65 pipe steel against hydrogen embrittlement. Fracture toughness after HCl immersion is determined with instrumented Charpy impact test. Fracture toughness is divided by 4 without inhibitor and only by 2 with, after 10 days of immersion. Optimum concentration of green inhibitor is found as 5%. Protection mechanism is due to a barrier of one or several molecular layers which prevent hydrogen atomic dissociation.